CoMn2O4 Nanoparticles Decorated on 2D MoS2 Frame: A Synergetic Energy Storage Composite Material for Practical Supercapacitor Applications. (March 2021) - Kanaujiya, Neha; Kumar, Nagesh; Singh, Meetesh; Sharma, Yogesh; Varma, G.D.
HIGHLIGHTS: Facile synthesis of mesoporous CoMn2 O4 @MoS2 nanocomposite. Content of MoS2 has been optimized to obtain best CoMn2 O4 @MoS2 nanocomposite. Best CoMn2 O4 @MoS2 sample shows specific capacitance of 422 F g −1 @ 0.5 A g −1 . Fabricated asymmetric supercapacitor exhibits maximum specific energy of 37 W hkg −1 . Such fabricated single asymmetric supercapacitor can light up a red LEDs for more than 3 min. Abstract: In material science, the synergistic effect comes into the picture when the physical and/or chemical properties of a composite material improve noticeably in comparison to that demonstrated by its forming individual components. This work represents the facile synthesis of CoMn2 O4 (CMO) and CoMn2 O4 @MoS2 (CMOS) nanocomposites via a co-precipitation synthesis approach. In this study, amounts of CMO precursors were kept constant and the effect of MoS2 addition on the electrochemical properties of the nanocomposite has been investigated. The substantial improvement in the electrochemical performance of the nanocomposite after adding MoS2 contents with CMO can be attributed to the synergistic effect. The CMOS nanocomposite synthesized using 20% MoS2 uniform dispersion (abbreviated as CMOS20) exhibits maximum improvement in the electrochemical properties which is ascribed to its higher specific surface area (74 m 2 g −1 ) and hierarchical pore size distribution. When examined in a conventional three-electrode system with 2 M KOH aqueous electrolyte, CMOS20 nanocomposite demonstrates high specific capacitances of 422 F g −1 at 0.5 A g −1, good cyclability, high-rate capability and higher diffusion coefficients (1.96 × 10 −10 cm 2 s −1 ). An asymmetric supercapacitor device designed using CMOS20 nanocomposite cathode and activated carbon anode exhibit maximum specific energy of 37 W h kg −1 and the maximum specific power of 5000 W kg −1 . This practical device can light up a red LED for more than 3 min. We believe the facile synthesis approach and promising electrochemical results assert the potential of our designed CMOS20 nanocomposite in the development of high-performance practical supercapacitor devices. Graphical Abstract: Demonstration of electrochemical properties of mesoporous CoMn2 O4 @MoS2 nanocomposite (CMOS20) and CMOS20//Activated Carbon (AC) asymmetric practical supercapacitor device. CMOS20//AC asymmetric supercapacitor shows maximum of 37 W h kg −1 specific energy and 5000 W kg −1 specific power. Image, graphical abstract